Experimental Study on the Performance of a Wind-Solar Hybrid Power Plant for Electric Motorcycle Charging Station Applications - Wicaksono, Yoga Arob; Trihatmojo, Ahmad Arbi (Universitas Muhammadiyah Metro, 2025)
The development of electric vehicle charging station infrastructure in Indonesia is still slow, resulting in difficulties for electric vehicle users due to limited driving range. On the other hand, Indonesia has a target of net zero emissions by 2050, while most of the energy sources for electric vehicle charging stations still rely on fossil fuels. To address this issue, innovative solutions such as electric vehicle charging stations powered by renewable energy are needed. Wind turbines and solar panels are technologies that can be utilized as energy sources. Power plants with a single energy source like solar panels have limitations in their energy production time. While wind turbines can operate 24 hours, they depend on wind speed. To overcome this problem, the solution is to implement a hybrid system by combining both wind and solar energy sources and converting them into electrical energy. This research aims to investigate the performance of a wind-solar hybrid power plant for electric vehicle charging station applications. The wind-solar hybrid power plant in this study is designed to provide electrical energy for one unit of an electric motorcycle with a battery capacity of 72 Volts 20 Ah. This research uses an experimental method in a real environment. The wind turbine used in this study is a cross-flow type, while the solar panel used is monocrystalline. To find the optimal point of the hybrid power plant system in converting energy, the influence of the number of turbine blades and the tilt angle of the solar panel on efficiency is investigated. The results show that a turbine with 6 blades can produce higher efficiency compared to turbines with 4 and 5 blades. Meanwhile, a tilt angle of 15o can produce higher efficiency compared to tilt angles of 0o and 30o.